Heavy Metal Content in Cosmetic Products and their Health Risk Assessment in the Libyan Market - Aborawi Elgornazi; Ezuldeen Aboshaloa (AlQalam Journal of Medical and Applied Sciences, 2026)
This study aimed to determine the concentrations of selected heavy metals (Pb, Cd, and Zn) in cosmetic products available on the Libyan market due to their potential health risks associated with prolonged exposure. Ten cosmetic samples, including face creams and lipsticks, were analyzed using atomic absorption spectrometry (AAS). Zinc was detected in all samples at concentrations ranging from 0.06 to 2.69 ppm and was the most abundant metal, likely attributable to its intentional use as an ingredient in cosmetic formulations. Lead concentrations ranged from <0.01 to 2.51 ppm, with the highest levels observed in lipstick samples, raising concerns regarding possible absorption through repeated application. Cadmium levels were consistently low in all samples (<0.1 ppm), indicating minimal contamination. All detected heavy metal concentrations were within internationally permissible limits. Moreover, health risk assessment revealed that the Target Hazard Quotient (THQ) and Hazard Index (HI) values for all samples were below unity, suggesting no significant non-carcinogenic health risk associated with the topical use of these cosmetic products.